Synthesis and characterization of a series of isoniazid hydrazones : Spectroscopic and theoretical study - Ferraresi Curotto, Verónica (2017)
A family of hydrazones of isoniazid and a group of hydroxybenzalaldehydes (vanillin, 5-bromovanillin, 5- chlorosalicylaldehyde and 5-bromosalicylaldehyde) were obtained and fully characterized. The results, including theoretical data, are comparatively analyzed along with the already reported hydrazone of ovanillin. The crystal structures of three compounds were determined. The hydrazones obtained from halogenated aldehydes are isomorphic and chiral to each other. Structures are further stabilized by (pyr) NHþ/Cl and OwH/Cl bonds. The vanillin hydrazone shows a conformer that differs from the previously reported. Neighboring molecules are linked to each other through OH/N(pyr) bonds, giving rise to a nearly planar polymeric structure. The conformational space was searched and geometries were optimized both in the gas phase and including solvent effects by DFT. Results are extended to describe the 5-bromovanillin hydrazone. FTIR, NMR and electronic spectra were measured and assigned with the help of computational calculations.